Carcinoma of the anal canal - David T. Marshall; Charles R. Thomas Jr (Frontiers Media S.A., 2011)
There are around 5,000 new cases of anal canal cancer each year in the United States. It is of particular risk in HIV-positive populations. Many cases are related to persistent infection with human papillomavirus (HPV). The treatment of anal cancer has progressed from abdominoperineal resection mandating permanent colostomy in the 1940s through the 1970s to modern chemoradiation with sphincter preservation in around 80% of patients, even with locally advanced disease. The evolution of the treatment paradigm of this disease is a model for the treatment of malignant disease with organ preservation. Multiple randomized trials have been conducted to guide this evolution. Technological developments in the delivery of radiotherapy and anti-cancer pharmaceuticals harbor hope for further improvements in outcomes with possible reductions in toxicity and increases in tumor control. Perhaps most inspiring is the recent development of HPV vaccines that